1977
DOI: 10.1136/hrt.39.9.967
|View full text |Cite
|
Sign up to set email alerts
|

Origin of ventricular reflexes caused by coronary arteriography.

Abstract: Left ventricular reflexes have in the past been investigated in anaesthetised animals, generally using an open chest technique. We have studied the degree of bradycardia occurring during coronary arteriography in 200 patients with a view to localising the origin of the ventricular reflexes. We have correlated the decrease of sinus rate with the anatomical distribution and integrity of the coronary tree. The degree of bradycardia was not influenced by the origin of the sinus node or the AV node arteries, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…2 ' 3 Further, these observations suggest that cardiac receptors mediating vasodepressor effects are preferentially distributed to the inferior wall of the heart in man. 2 Myocardial necrosis in dogs 4 and coronary occlusion in cats 5 ' 6 are known to activate cardiac receptors and to induce reflex responses 7 …”
mentioning
confidence: 83%
“…2 ' 3 Further, these observations suggest that cardiac receptors mediating vasodepressor effects are preferentially distributed to the inferior wall of the heart in man. 2 Myocardial necrosis in dogs 4 and coronary occlusion in cats 5 ' 6 are known to activate cardiac receptors and to induce reflex responses 7 …”
mentioning
confidence: 83%
“…Clinical and experimental data have shown that the Bezold-Jarisch reflex plays an important role in the control of cardiovascular function in normal and pathophysiological conditions (41)(42)(43). An indication of the functional role of this reflex in cardiovascular regulation was reported by Chianca Jr. and Machado (44), demonstrating an increased sensitivity of the Bezold-Jarisch reflex in both acute and chronic sinoaortic denervated rats (Figure 3).…”
Section: Cardiopulmonary Reflexesmentioning
confidence: 73%
“…On the other hand, when spontaneous angina was accompanied by a decrease in heart rate and systemic arterial pressure, ST segment changes were observed in inferior and inferolateral leads (table I). These two types of cardiovascular response frequently occur within 30-60 min after the onset of myocar dial infarction [10] and during coronary an giography [11] or coronary spasm [12], Time intervals during spontaneous an gina were differently affected in these two groups of patients. The number of patients included in each group is relatively small, since criteria of spontaneous angina in the invasive laboratory are difficult to meet; however, we believe that the results are fairly convincing, since changes during and after angina are quite consistent.…”
Section: Discussionmentioning
confidence: 99%